Variations in institutional review board processes and consent requirements for trauma research: an EAST multicenter survey. Issue 1 (30th May 2018) - Nahmias, Jeffry; Grigorian, Areg; Brakenridge, Scott; Jawa, Randeep S; Holena, Daniel N; Agapian, John Varujan; Bruns, Brandon; Chestovich, Paul J; Chung, Bruce; Nguyen, Jonathan; Schulman, Carl I; Staudenmayer, Kristan; et al.
Abstract : Oversight of human subject research has evolved considerably since its inception. However, previous studies identified a lack of consistency of institutional review board (IRB) determination for the type of review required and whether informed consent is necessary, especially for prospective observational studies, which pose minimal risk of harm. We hypothesized that there is significant inter-institution variation in IRB requirements for the type of review and necessity of informed consent, especially for prospective observational trials without blood/tissue utilization. We also sought to describe investigators' and IRB members' attitudes toward the type of review and need for consent. Eastern Association for the Surgery of Trauma (EAST) and IRB members were sent an electronic survey on IRB review and informed consent requirement. We performed descriptive analyses as well as Fisher's exact test to determine differences between EAST and IRB members' responses. The response rate for EAST members from 113 institutions was 13.5%, whereas a convenience sample of IRB members from 14 institutions had a response rate of 64.4%. Requirement for full IRB review for retrospective studies using patient identifiers was reported by zero IRB member compared with 13.1% of EAST members (p=0.05). Regarding prospective observational trials without blood/tissue collection, 48.1% of EAST members reported their institutions required a full IRB review compared with 9.5% of IRB members (p=0.01). For prospective observational trials with blood/tissue collection, 80% of EAST members indicated requirement to submit a full IRB review compared with only 13.6% of IRB members (p<0.001). Most EAST members (78.6%) stated that informed consent is not ethically necessary in prospective observational trials without blood/tissue collection, whereas most IRB members thought that informed consent was ethically necessary (63.6%, p<0.001). There is significant variation in perception and practice regarding the level of review for prospective observational studies and whether informed consent is necessary. We recommend future interdisciplinary efforts between researchers and IRBs should occur to better standardize local IRB efforts. Level of evidence: IV.